Lane formation in confined cation mixtures in strong DC electric fields - Marañon Di Leo, Julio (2011)
On applying an external electric potential field at the ends of a flexible nanopore, the resulting onward current flow parallel to the field has been simulated with molecular dynamic simulation. This is suitable to study different effects of self-organisation, such as lane formation. The electrolyte model was composed of three Na+/K+ (30/70, 50/50 and 70/30) concentration ratios in aqueous solutions.